Association between sleep duration and incidence of type 2 diabetes in China: the REACTION study. Issue 10 (20th May 2022) - Liu, Hongzhou; Chen, Gang; Wen, Junping; Wang, Anping; Mu, Yimin; Dou, Jingtao; Gu, Weijun; Zang, Li; Zhang, Saichun; Lyu, Zhaohui
Abstract: Backgrounds: Inadequate sleep duration is associated with a higher risk of type 2 diabetes and the relationship is nonlinear. We aim to assess the curve relationship between night sleep duration and the incidence of type 2 diabetes in China. Methods: A cohort of 11, 539 participants from the REACTION study without diabetes at baseline (2011) were followed until 2014 for the development of type 2 diabetes. The average number of hours of sleep per night was grouped. Incidence rates and odds ratios (ORs) were calculated for the development of diabetes in each sleep duration category. Results: Compared to people who sleep for 7 to 8 h/night, people with longer sleep duration (≥9 h/night) had a greater risk of type 2 diabetes (OR: 1.27; 95% CI: 1.01–1.61), while shorter sleep (<6 h/night) had no significant difference in risk of type 2 diabetes. When the dataset was stratified based on selected covariates, the association between type 2 diabetes and long sleep duration became more evident among individuals <65 years of age, male, body mass index <24 kg/m 2 or with hypertension or hyperlipidemia, no interaction effects were observed. Furthermore, compared to people persistently sleeping 7 to 9 h/night, those who persistently slept ≥9 h/night had a higher risk of type 2 diabetes. The optimal sleep duration was 6.3 to 7.5 h/night. Conclusions: Short or long sleep duration was associated with a higher risk of type 2 diabetes. Persistently long sleep duration increased the risk.